Youtube Videos For Listening Skills During Covid-19 Pandemic: EFL Students’ Views - Audina, Ira Putri; Artini, Luh Putu; Dewi, Ni Luh Putu Eka Sulistia; Suwastini, Ni Komang Arie (Universitas Pendidikan Ganesha, 2022)
Social media acts as a source of information, entertainment media, discussion space, enriching learning resources, increasing creativity, and increasing student understanding, allowing students to create awareness about students' potential to become intellectually active. The most common social media used in EFL classrooms are Facebook, Whatsapp, YouTube, Instagram, and Twitter. Many have argued that YouTube provides authentic learning sources for improving students' English skills. Despite the availability and authenticity of YouTube videos to provide practice in enhancing students' listening skills, especially in an online setting, its application serves some challenges. The present study aimed to explore the students' perception of the application of YouTube in listening classes during online learning. This study was a qualitative study involving 32 university students. Data were collected from a questionnaire consisting of 31 items distributed through Google Form. The analysis resulted in students’ positive perception in the forms of four benefits: improving listening skills, increasing interest and motivation to learn, building critical thinking, and sharpening creativity. The identified shortcomings are the internet connection and the expensive internet credit. The present study confirms the usability of YouTube videos to practice students' listening skills, especially in online learning, where students need flexibility and creativity. However, it implies suggestions for stakeholders to provide stable and affordable internet connections so online learning can be conducted more effectively.